Psychological Health of Pregnant Women Experiencing Domestic Violence in Central Punjab - Rukhsar Fatima; Tahira Parveen; Abdul Junaid; Jawwad Muhammad Shujaat (Pakistan Armed Forces Medical Journal, 2024)
Objective: To evaluate the impact of domestic violence on the psychological health of pregnant women. Study Design: Cross-sectional study. Place and Duration of Study: The study was conducted public and private hospitals in Central Punjab, specifically in the districts of Sargodha, Khushab, and Jauharabad, Pakistan, from Jan 2022 to Apr 2023. Methodology: A purposive sampling technique was employed to collect the data. The Domestic Violence Scale for intimate partner violence and the Psychological Distress Scale for adults were utilized for data collection. Demographic variables recorded included name, age, number of children, residential area, and profession. Results: The sample for the research comprised (n=250) pregnant women, further categorized into primigravida (n=138) and multigravida (n=112) from Central Punjab, Pakistan. The age range of the participants was 18-45 years. Two self-report measures, the Domestic Violence Scale for intimate partner and the Psychological Distress Scale for adults were used to measure the constructs of the present study. Conclusion: The overall findings revealed that domestic violence is a significant predictor of psychological distress among pregnant women. Furthermore, the findings indicated that there were no significant mean differences in psychological health, anxiety, depression, and stress between the two groups.